Building ‘Entrepreneurial Mindset’ through Writing Ability in the EFL Classrooms - Ahmad Heki Sujiatmoko; Lestari Setyowati (ELITE Association Indonesia, 2023)
ABSTRACTMany educated people are found to be unemployed due to lacks of the job vacancy provided in accordance with their background knowledge at university or college. This can be a serious problem entailing the failure of building economic growth in society. This study investigated the students’ entrepreneurial mindset seen from their essay writing products. This study also used a cross-sectional design. There were 25 subjects from English department of the Faculty of Letters, Universitas Negeri Malang. The instruments used were a questionnaire and a depth-interview. The results showed that most of the students did not have a good motivation, intention, and experience in doing business due to some factors like having no permission from the parents, no skills for practicing business, no social networks in business, and also feeling taboo to connect education with business in the life. However, the students’ writing performance were mostly good. The study implies that entrepreneurial mindset can be the alternative topic to support the students’ writing skill and be the solutions for leading them to be prosperous people with a bright future behind their education level. Keywords: Entrepreneurial mindset, Writing ability, EFL classrooms